(untitled) (SAARC Journal of Agriculture, 2014)
A field experiment was conducted for two years (2007 and 2008) at the G. B. Pant University of Agriculture and Technology, Pantnagar, to study the productivity, biological efficiency and economics of intercropping in spring maize (Zea mays L.) with sunflower (Helianthus annuus L.) and urdbean (Vigna mungo L.) under different spatial arrangements. The experiment consisting of ten treatments i.e. three sole crops (maize, sunflower and urdbean), six replacement intercropping system of maize with each sunflower and urdbean in row ratios of 1:1, 2:1 and 3:1 and one additive intercropping system of maize with urdbean in row ratios of 1+1 was laid out in randomized block design with three replications. The intercropping system of maize with urdbean in row ratio (1+1) was found beneficial over sole cropping of maize and gave the maximum maize-equivalent yield (5847 kg ha-1), land-equivalent ratio (1.36) and net return (Rs.13420 ha-1). Intercropping of maize in replacement arrangement was not productive and advantageous than respective sole crops. DOI: http://dx.doi.org/10.3329/sja.v12i1.21110 SAARC J. Agri., 12(1): 26-32 (2014)